The genomic copy number determination of improved Cre in transgenic mice using standards derived from megaprimer PCR constructed tandem repeats - Ge Diao; Min Tian; Runbo Li; Jie Huang; Jian Han; Jianxin Guo (All Life)
Determination of the genomic copy number of Cre transgene is critical for the establishment of transgenic animal models. We demonstrate a real-time quantitative polymerase chain reaction (RT-qPCR) based method for genomic copy number determination of improved Cre (iCre), which was tested in a transgenic mouse model of CYP19A1-iCre. The standards were derived from tandem repeats of iCre fragments which were constructed by a new application of megaprimer PCR. Two rounds of megaprimer PCR were used to obtain specific tandem repeats of iCre fragments, which were subsequently cloned into pUCm-T vectors. After the fragments of IL-2 (reference gene) were ligated into the same vectors, standards with copy number ratios (CNR) of 0.5, 1, 2, 4, 8, and 16 between iCre and IL-2 were completed. The R2 values of the standard curves exceeded 0.99. The calculated CNR value of the quality control sample was satisfactory. Multiple copies of iCre were detected in founder mice. After several passages, the copy number of iCre gradually decreased to a single copy, which was consistent with theoretical expectation. The established method is a universal and sensitive program for genomic copy number determination of iCre in transgenic mice.